Phenotypes of conjunctival inflammatory cells in sarcoidosis. Issue 2 (February 1992) - Karma, A; Taskinen, E; Kainulainen, H; Partanen, M
Abstract : Phenotypes of the infiltrating mononuclear cells of the lower fornix conjunctiva of nine patients with sarcoidosis and six controls were studied using monoclonal antibodies and a modified immunoperoxidase method. Four patients had sarcoidosis of recent onset (duration of 2 years or less) and five patients had a chronic disease (duration of 3 or more years). The inflammatory cells in the sarcoid conjunctival specimens were predominantly T lymphocytes, the vast majority of which were of T helper/inducer subtype expressing Leu-3a + 3b positivity. The ratio of T helper/inducer cells to T suppressor/cytotoxic cells was 3.9 on average but only 0.9 in controls. Epithelioid cell granulomas were seen in three specimens in one case of recent onset and in two chronic cases comprising a marked amount (more than 15 cells/visual field) of cells bearing phenotypes of macrophages, T cells, T helper/inducer cells and HLA-DR antigen, and in smaller quantities of T suppressor/cytotoxic cells. The mean number of all immunocompetent cell subtypes of specimens from newly diagnosed patients exceeded that of specimens from chronic patients. We believe that the sarcoid immune reaction in the conjunctiva is a dynamic process in which proliferation of immunocompetent mononuclear cells precedes the stage of granuloma formation.